Phaseolus vulgaris MIR1511 genotypic variations differentially regulate plant tolerance to aluminum toxicity. (31st January 2021) - Ángel Martín‐Rodríguez, Jose; Ariani, Andrea; Leija, Alfonso; Elizondo, Armando; Fuentes, Sara I.; Ramirez, Mario; Gepts, Paul; Hernández, Georgina; Formey, Damien
SUMMARY: The common‐bean ( Phaseolus vulgaris ), a widely consumed legume, originated in Mesoamerica and expanded to South America, resulting in the development of two geographically distinct gene pools. Poor soil condition, including metal toxicity, are often constraints to common‐bean crop production. Several P. vulgaris miRNAs, including miR1511, respond to metal toxicity. The MIR1511 gene sequence from the two P. vulgaris model sequenced genotypes revealed that, as opposed to BAT93 (Mesoamerican), the G19833 (Andean) accession displays a 58‐bp deletion, comprising the mature and star miR1511 sequences. Genotyping‐By‐Sequencing data analysis from 87 non‐admixed Phaseolus genotypes, comprising different Phaseolus species and P. vulgaris populations, revealed that all the P. vulgaris Andean genotypes and part of the Mesoamerican (MW1) genotypes analyzed displayed a truncated MIR1511 gene. The geographic origin of genotypes with a complete versus truncated MIR1511 showed a distinct distribution. The P. vulgaris ALS3 ( Aluminum Sensitive Protein 3 ) gene, known to be important for aluminum detoxification in several plants, was experimentally validated as the miR1511 target. Roots from BAT93 plants showed decreased miR1511 and increased ALS3 transcript levels at early stages under aluminum toxicity (AlT), while G19833 plants, lacking mature miR1511, showed higher and earlier ALS3 response. Root architecture analyses evidenced higher tolerance of G19833 plants to AlT. However, G19833 plants engineered for miR1511 overexpression showed lower ALS3 transcript level and increased sensitivity to AlT. Absence of miR1511 in Andean genotypes, resulting in a diminished ALS3 transcript degradation, appears to be an evolutionary advantage to high Al levels in soils with increased drought conditions. Significance Statement: miR1511 is differentially distributed among Phaseolus species and genotypes, and regulates ALS3 transcript, known to be important for aluminum detoxification in plants. The absence of miR1511 in Andean genotypes, resulting in a diminished ALS3 transcript degradation, appears to be an evolutionary advantage to high Al levels in soils with increased drought conditions.